Sustainability, energy and architecture : case studies in realizing green buildings - Sayigh, Ali (Academic Press, 2014)
This unique volume offers insights from renowned experts in energy efficient building from the world over, providing a multi-faceted overview of the state-of-the-art in energy efficient architecture. It opens by defining what constitutes a sustainable building, suggesting bases for sorely needed benchmarks, then explains the most important techniques and tools available to engineers and architects exploring green building technologies. It covers such pivotal issues as daylighting, LED lighting, integrating renewables such as solar thermal and cooling, retrofitting, LEED and similar certification efforts, passive houses, net-zero and close-zero structures, water recycling, and much more. Highlighting best practices for commercial buildings and private homes, in widely varied climates and within vastly different socio-economic contexts, this illustrated reference will guide architects and engineers in making sustainable choices in building materials and methods. Explains the best methods and materials to support energy efficient building Features case studies by experts from a dozen countries, demonstrating how sustainable architecture can be achieved in varied climates and economies Covers both new constructions and retrofitting of existing structures.